A responsabilidade civil do empregador na Síndrome de Burnout - Moraes, Paulo Ricardo Dias de (2024)
Due to its fundamental importance in a person's life, a significant portion of human life is directed towards preparation and commitment to work. In recent years, there has been greater attention to the effect of work on physical and mental health, with emphasis on Burnout syndrome, which highlights many of the consequences of professional activities on the worker and, consequently, on the organization. Burnout syndrome arises as a response to chronic occupational exhaustion, resulting from a work environment that has not been adequately managed. When this syndrome manifests itself in an employee due to inadequate management of the work environment, it is important to reflect on the dynamics between the employee and his/her work environment, especially when the necessary support is not perceived by the employer. In this context, taking into account that degraded work environments have consequences for workers, this Dissertation aims to investigate the employer's responsibility in the emergence of Burnout Syndrome. Regarding the methodology, the research adopts a qualitative approach, since the researcher's interpretation plays a fundamental role. Furthermore, regarding the objectives, the research is exploratory in nature, as it aims to clarify concepts and offer a comprehensive view of the topic. This demonstrates that this Dissertation enriches the understanding and improvement of a specific subject, presented in a dissertative-argumentative form and supported by an extensive bibliographic review, both from national and international sources. In view of what was presented, we sought to address the current regulations and the civil liability of the employer in cases of damages caused, whether by their actions or omissions with regard to safety and health in the workplace. In this sense, we argue that the worker's right to a healthy environment must be in line with labor rights and fundamental rights. Furthermore, it is essential to recognize that every individual has the right to a dignified and healthy work environment, as well as the freedom not to be disturbed by anyone, especially by the employer. In this context, it is essential to emphasize that work is only one of the many dimensions of human rights and human dignity. At no time does a worker cease to be human as a result of work, since their condition as a human being cannot be dissociated from the sale of their labor force. Therefore, it is crucial that their dignity be fully preserved and protected, since professional activity is an essential part of their existence. Thus, the profession must be based on dignity, which must be understood as the "foundation of all human activity". Finally, as discussed, it is a worker's right to have access to a healthy work environment. The employer's sole responsibility lies in ensuring that all safety and hygiene protocols are strictly followed, aiming to avoid any type of physical, cognitive or emotional harm.